Clinical characteristics and cognitive function in bipolar disorder patients with different onset symptom - Wang, Zhonggang; Cao, Haiyan; Cao, Yuying; Song, Haining; Jiang, Xianfei; Wei, Chen; Yang, Zhenzhen; Li, Jie (Frontiers in Psychiatry, 2023)
Aim: To assess the cognitive functions of patient' s index episode of bipolar disorder, depression or mania, on risk factors of effecting on cognitive functions. Method: 168 patients with bipolar disorder for the first time were enrolled in the study . All patients were divided into two groups according to their index episode of bipolar disorder, either depression or mania . 73 patients had an index episode mania and 96 patients had initial symptoms of depression .75 healthy controls were included . Demographic or clinical disease characteristic data of all enrolled patients were collected . The cognitive functions of all patients and controls were detected by continuous performance test( CPT) , digital span test( DST) and Wisconsin card sorting test( WCST) . Result: ( 1) Most patients with bipolar disorder had an index episode depression[56 .55% vs . 43 .45%] . Compared with the depression group, the mania group had later age of onset [P = 0 .035] . The education level of patient groups was lower than control group ( P < 0 .001) .(2) The healthy control group's DST, WCST and CPT scores were better than the patient groups ( All P < 0. 0 5) . The mania group's DST, WCST, CPT was better than the depression group (P< 0 .0 5 ) . (3 ) In mania group, CPT parameter, inverse digit span, and the sum of DST was negatively correlated with the education level ( All P < 0 .0 5 ) . The CPT-4 -digit score was negatively correlated with onset age( P < 0 . 0 5 ) . In depression group, there was a positive correlation between inverse digit span and the education level(P < 0.05). Conclusion: There were cognitive impairments in attention, memory, and executive function of patients with different onset syndromes of bipolar disorder. The degree of cognitive impairments in bipolar patients with the depressive episode was more severe . The risk factors affecting cognitive impairments included the age of onset, education level, number of hospitalizations and severity of illness .